Exploring EFL Students In Think Pair And Share Practice In Reading Classroom: A Case Study - Azizah, Savira Nur; Pahlevi, Muhammad Reza; Ridwan, Iwan (Peneliti.net, 2024)
A good understanding can be a bridge for students to have exemplary learning achievements in their learning process. The introduction of practical learning methods in developing reading skills in English is a challenge that educators continue to face. to explore students' experiences in applying the Think-Pair-Share method in the context of learning to read in EFL classes. This research will focus on students' behavior of the Think-Pair-Share process, their responses to interactions in pairs, and the impact of using this method on their reading skills. The researcher used case study design to conduct this research. To analyze the data, the researcher adopted the thematic analysis. The participants in this study consisted of 7th-grade students at a junior high school in Karawang. The results indicated that students actively participated in discussions, asked questions, and paid attention to the teacher. This positive attitude was also evident in the improved quality of learning assignment outcomes. In learning to read English, the involvement of students in interactions and discussions illustrated the significance of this method.